Generation Impact, Updated and Expanded Edition - Goldseker, Sharna; Moody, Michael (Wiley, 2020)
An insider's guide to the coming philanthropic revolution Meet the next generation of big donors-the Gen X and Millennial philanthropists who will be the most significant donors ever and will shape our world in profound ways. Hear them describe their ambitious plans to revolutionize giving so it achieves greater impact. And learn how to help them succeed in a world that needs smart, effective donors now more than ever. As "next gen donors" step into their philanthropic roles, they have not only unprecedented financial resources, but also big ideas for how to wield their financial power. They want to disrupt the traditional world of charitable giving, and they want to do so now, not after they retire to a life of philanthropic leisure. Generation Impact: How Next Gen Donors Are Revolutionizing Giving pulls back the curtain on these rising next gen donors and the "Impact Revolution" they seek, offering extensive firsthand accounts and expert analysis of their hands-on, boundary-pushing strategies, as well as their determination to honor the legacies they've inherited and the values they hold. This Updated and Expanded edition includes new, practical resources designed to help those who work with next gen donors to engage with them in even more productive and effective ways - to help them become the sort of transformational donors we all need them to be in this pivotal time. Three Best Practice Guides offer targeted tips for key audiences - nonprofits and fundraisers, families, and advisors - and introduce new data and additional featured donors. A new Preface answers the most pressing questions asked by the thousands of readers already energized by Generation Impact, including what has changed in the world in recent years and how these influential emerging donors are responding. Adapting to the revolution that next gen donors are bringing may not be easy, but this book can help